Identification of mental model and prediction of class XII high school students on the topic of convection heat transfer - Widia Linta Nurjanah; Ika Mustika Sari; Duden Saepuzaman (Universitas PGRI Kanjuruhan Malang, 2024)
Mental models have an important role in the learning process because learning in general can be seen as mental modeling. The purpose of this study is to identify students' mental models and identify the relationship between mental models and prediction ability on the topic of convection heat transfer. The sample of this study was 15 on 12th-grade high school students, 8 male students and 7 female students. The students came from three different schools, namely from Tasikmalaya district, Ciamis district, and Banjar City. Sampling was done by purposive sampling with the characteristics of students who have studied heat and students who have high cognitive process abilities in their respective schools. Data collection was done by semi-structured interviews with the type of questions in the form of content and prediction. Data analysis is done by constant comparative method. The results of this study show that there are no students who have a scientific mental model. Five types of mental models were found, including unclear model, convection is a continuation of conduction, convection that does not change density, convection for evaporation, and model 3. In addition, the relationship between prediction and mental model was classified as complex. This is due to students who predict without using their mental models. Knowing the diverse mental models of students, educators become more knowledgeable about the level of representation of each student. So that educators can prepare appropriate learning strategies in order to construct students' mental models.